Identity and violence : the illusion of destiny - Sen, Amartya, 1933- (New York : W.W. Norton & Co., 2006)
"Sen argues in this book that conflict and violence are sustained today, no less than in the past, by the illusion of a unique identity. Indeed, the world is increasingly taken to be a federation of religions (or of "cultures" or "civilizations"), ignoring the relevance of other ways in which people see themselves, involving class, gender, profession, language, literature, science, music, morals, or politics. Global attempts to stop such violence are also handicapped by the conceptual disarray generated by the presumption of singular and choiceless identity. When relations among different human beings are identified with a "clash of civilizations," or alternatively, with "amity among civilizations," human beings are miniaturized and deposited into little boxes." "Through his investigation of such diverse subjects as multiculturalism, postcolonialism, fundamentalism, terrorism, and globalization, Sen brings out the need for a clearheaded understanding of human freedom and the effectiveness of constructive public voice in global civil society. The world, Sen shows, can be made to move toward peace as firmly as it has recently spiraled toward violence and war."--Jacket
The violence of illusion -- Making sense of identity -- Civilizational confinement -- Religious affiliations and Muslim history -- West and anti-west -- Culture and captivity -- Globalization and voice -- Multiculturalism and freedom -- Freedom to think
Includes bibliographical references (pages 187-197) and indexes
Keywords: Identity (Philosophical concept); Group identity; Violence; Social Identification; Violence